Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To determine which ordered pair makes both inequalities true, we need to check each pair against the two given inequalities:
1. [tex]\( y < 3x - 1 \)[/tex]
2. [tex]\( y \geq -x + 4 \)[/tex]
Let’s evaluate each pair one by one.
### For the pair [tex]\((4, 0)\)[/tex]:
1. Substitute [tex]\(x = 4\)[/tex] and [tex]\(y = 0\)[/tex] into the first inequality:
[tex]\[ 0 < 3(4) - 1 \][/tex]
[tex]\[ 0 < 12 - 1 \][/tex]
[tex]\[ 0 < 11 \][/tex]
This inequality is true.
2. Substitute [tex]\(x = 4\)[/tex] and [tex]\(y = 0\)[/tex] into the second inequality:
[tex]\[ 0 \geq -4 + 4 \][/tex]
[tex]\[ 0 \geq 0 \][/tex]
This inequality is true as well.
Since both inequalities are satisfied, [tex]\((4, 0)\)[/tex] makes both inequalities true.
### For the pair [tex]\((1, 2)\)[/tex]:
1. Substitute [tex]\(x = 1\)[/tex] and [tex]\(y = 2\)[/tex] into the first inequality:
[tex]\[ 2 < 3(1) - 1 \][/tex]
[tex]\[ 2 < 3 - 1 \][/tex]
[tex]\[ 2 < 2 \][/tex]
This inequality is false.
Since the first inequality is not satisfied, we don't need to check the second inequality for this pair. [tex]\((1, 2)\)[/tex] does not make both inequalities true.
### For the pair [tex]\((0, 4)\)[/tex]:
1. Substitute [tex]\(x = 0\)[/tex] and [tex]\(y = 4\)[/tex] into the first inequality:
[tex]\[ 4 < 3(0) - 1 \][/tex]
[tex]\[ 4 < -1 \][/tex]
This inequality is false.
Since the first inequality is not satisfied, we don't need to check the second inequality for this pair. [tex]\((0, 4)\)[/tex] does not make both inequalities true.
### For the pair [tex]\((2, 1)\)[/tex]:
1. Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 1\)[/tex] into the first inequality:
[tex]\[ 1 < 3(2) - 1 \][/tex]
[tex]\[ 1 < 6 - 1 \][/tex]
[tex]\[ 1 < 5 \][/tex]
This inequality is true.
2. Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 1\)[/tex] into the second inequality:
[tex]\[ 1 \geq -2 + 4 \][/tex]
[tex]\[ 1 \geq 2 \][/tex]
This inequality is false.
Since the second inequality is not satisfied, [tex]\((2, 1)\)[/tex] does not make both inequalities true.
Based on the evaluation, the ordered pair that makes both inequalities true is [tex]\((4, 0)\)[/tex].
1. [tex]\( y < 3x - 1 \)[/tex]
2. [tex]\( y \geq -x + 4 \)[/tex]
Let’s evaluate each pair one by one.
### For the pair [tex]\((4, 0)\)[/tex]:
1. Substitute [tex]\(x = 4\)[/tex] and [tex]\(y = 0\)[/tex] into the first inequality:
[tex]\[ 0 < 3(4) - 1 \][/tex]
[tex]\[ 0 < 12 - 1 \][/tex]
[tex]\[ 0 < 11 \][/tex]
This inequality is true.
2. Substitute [tex]\(x = 4\)[/tex] and [tex]\(y = 0\)[/tex] into the second inequality:
[tex]\[ 0 \geq -4 + 4 \][/tex]
[tex]\[ 0 \geq 0 \][/tex]
This inequality is true as well.
Since both inequalities are satisfied, [tex]\((4, 0)\)[/tex] makes both inequalities true.
### For the pair [tex]\((1, 2)\)[/tex]:
1. Substitute [tex]\(x = 1\)[/tex] and [tex]\(y = 2\)[/tex] into the first inequality:
[tex]\[ 2 < 3(1) - 1 \][/tex]
[tex]\[ 2 < 3 - 1 \][/tex]
[tex]\[ 2 < 2 \][/tex]
This inequality is false.
Since the first inequality is not satisfied, we don't need to check the second inequality for this pair. [tex]\((1, 2)\)[/tex] does not make both inequalities true.
### For the pair [tex]\((0, 4)\)[/tex]:
1. Substitute [tex]\(x = 0\)[/tex] and [tex]\(y = 4\)[/tex] into the first inequality:
[tex]\[ 4 < 3(0) - 1 \][/tex]
[tex]\[ 4 < -1 \][/tex]
This inequality is false.
Since the first inequality is not satisfied, we don't need to check the second inequality for this pair. [tex]\((0, 4)\)[/tex] does not make both inequalities true.
### For the pair [tex]\((2, 1)\)[/tex]:
1. Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 1\)[/tex] into the first inequality:
[tex]\[ 1 < 3(2) - 1 \][/tex]
[tex]\[ 1 < 6 - 1 \][/tex]
[tex]\[ 1 < 5 \][/tex]
This inequality is true.
2. Substitute [tex]\(x = 2\)[/tex] and [tex]\(y = 1\)[/tex] into the second inequality:
[tex]\[ 1 \geq -2 + 4 \][/tex]
[tex]\[ 1 \geq 2 \][/tex]
This inequality is false.
Since the second inequality is not satisfied, [tex]\((2, 1)\)[/tex] does not make both inequalities true.
Based on the evaluation, the ordered pair that makes both inequalities true is [tex]\((4, 0)\)[/tex].
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.